COMPARISON OF THE SENSITIVITY AND SPECIFICITY OF THE ZIEHL-NEELSEN METHOD WITH THE MOLECULAR RAPID TEST METHOD IN THE EXAMINATION OF BTA IN THE SPUTUM OF PATIENTS SUSPECTED OF PULMONARY TUBERCULOSIS - Roswidianah, Erna; Diana, Sulis; Anggreni, Dhonna (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Pulmonary tuberculosis or pulmonary TB is a disease that is easilytransmitted through the air from the source of transmission, namely BTA positiveTB patients when coughing or sneezing, patients spread germs into the air in theform of sputum splashes. For this reason, an examination method that has highsensitivity and specificity is needed as a tool for early detection of Pulmonary TB.Research Objective: To study the comparison of the sensitivity and specificity ofthe Ziehl-neelsen method and the Molecular Rapid Test method in examining BTAin the sputum of TB suspected patients at the Puskesmas against the gold standardusing BTA culture.This study is an analytic observational study with a cross sectional design.The population in this study were all patients suspected of having Pulmonary TBwho came to the Kupang Health Center, Jetis Health Center, and Gedeg HealthCenter who performed microscopic and culture examinations in the laboratoryduring 2023. Sample selection used simple random sampling method with a samplesize of 60 patients. The hypothesis was proven using the Kappa test.Results: the sensitivity and specificity of the Ziehl-Neelsen method BTAexamination were 60% and 100%, while the sensitivity and specificity of theMolecular Rapid Test method examination were 100% and 100%. The results ofthe Cohen's Kappa test showed that between the Ziehl-Neelsen and MolecularRapid Test methods both had high sensitivity and specificity (Kappa; 0.733).Conclusions and advice: Based on the results of the study, the molecularrapid test method has a higher sensitivity than the Ziehl-Neelsen method. Thismethod can be recommended for early detection of pulmonary TB